THU0001 Variation in granzyme-b is associated with progression of joint destruction in rheumatoid arthritis. (23rd January 2014) - Knevel, R.; Krabben, A.; Wilson, G.; Brouwer, E.; Lindqvist, E.; de Rooy, D.; Daha, N.; van der Linden, M.; Tsonaka, R.; Zhernakova, S.; Westra, H.-J.; Franke, L.; et al.
Abstract : Background: The severity of joint destruction in Rheumatoid Arthritis (RA) is highly variable between patients and 45-58% of the variance is estimated to be explained by genetic factors. The serine proteinase Granzyme-B (GZMB) is important for the rapid induction of target cell apoptosis by cytotoxic T-cells and several in vitro studies suggested that GZMB is involved in apoptosis of chondrocytes. GZMB serum levels are increased in RA and the height of these levels are associated with higher risk of radiographic erosions. Objectives: To investigate GZMB as a candidate gene for the severity of the rate of joint destruction in RA. Methods: 1, 418 patients with 4, 885 X-ray sets of both hands and feet of four independent datasets were studied. First, explorative analyses were performed on 600 RA-patients enrolled in the Leiden-Early-Arthritis-Clinic. 16 SNPs tagged GZMB and were tested. Significantly associated SNPs were genotyped in datasets from Groningen (NL), Sheffield (UK) and Lund (Sw). In each dataset the relative increase of the progression rate per year in the presence of a genotype was assessed. Subsequently, data were summarized in a meta-analysis. To assess the functional potential of GZMB, the association of the identified SNPs with RNA-expression level of the genomic region of GZMB was tested, by mapping expression quantitative trait locus (eQTL) on 1, 469 whole blood samples. Results: In the discovery cohort, patients homozygous for the minor allele of rs8192916 had a 1.05 (95%CI 1.02-1.08) fold rate of joint destruction per year compared to other patients ( P =1.2×10 -3 ). Thisassociation remained significant in the meta-analysis on all datasets ( P =7.8×10 -4 ). eQTL of GZMB tested a higher expression in the presence of the minor allele of rs8192916 ( P =2.2×10 -5 ). Conclusions: Rs8192916 located in GZMB is associated with the progression of joint destruction in RA as well as with RNA expression levels in whole blood. Future studies are needed to evaluate whether rs8291916, or a genetic variant linked to this SNP, is associated with an enhanced destructive process or with propagation of the immune response, to further explain the observations done on DNA and RNA levels in RA. Disclosure of Interest: None Declared